AL-QURAN SEBAGAI KITAB TERBUKA UNTUK LANDASAN PENGEMBANGAN TAFSIR PENDIDIKAN - Bahrun Ulum (Journal Khafi : Journal Of Islamic Studies, 2025)
The spirit of Al-Quran is the spirit of progress. This includes education. Al-Quran also needs to be understood by the spirit of its time based on universal basic values and principles. Al-Quran can be understood if there is an effort to think and study its contents. Al-Quran, as an inclusive text or living text, opens a dialogue with the recipient of the message. We are encouraged to carry out serious, productive reading in an effort to reveal the meaning and significance of educational verses in order to develop Tafsir Tarbawi, both theoretical and practical, on education as a treasure and solution to current situations.